2016
DOI: 10.4102/sajbm.v47i1.53
|View full text |Cite
|
Sign up to set email alerts
|

Measuring business schools’ service quality in an emerging market using an extended SERVQUAL instrument

Abstract: An extended SERVQUAL instrument is developed, validated and used to measure perceived service quality delivered to students by business schools in an emerging market economy. A longitudinal survey is conducted with selected students in their final year of study from two business schools in an emerging market economy. The use of the extended SERVQUAL model is suggested to monitor student/employee expectations and perceptions during and after the education service delivery process. Students attach different weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…The SERVQUAL instrument by Parasuraman et al (1988) is the most popular tool among researchers, followed by SERVPERF by Cronin and Taylor (1992) and HEdPERF by Abdullah (2006b). SERVQUAL and SERVPERF have been used as the measurement of SQ in a plethora of empirical studies ( -Donlagi c and Fazli c, 2015;Galeeva, 2016;Mbise and Tuninga, 2016). However, little attention has been given to qualitative aspects of SQ in HEIs; especially SQ from students' perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…The SERVQUAL instrument by Parasuraman et al (1988) is the most popular tool among researchers, followed by SERVPERF by Cronin and Taylor (1992) and HEdPERF by Abdullah (2006b). SERVQUAL and SERVPERF have been used as the measurement of SQ in a plethora of empirical studies ( -Donlagi c and Fazli c, 2015;Galeeva, 2016;Mbise and Tuninga, 2016). However, little attention has been given to qualitative aspects of SQ in HEIs; especially SQ from students' perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Often such analyses is too long according to customers, it contains difficult terms, so they do not want to waste their time. Very often they fill in surveys carelessly, answer questions randomly or interrupt the study when they get bored (Ciavolino & Calcagni, 2015;Gołąb-Andrzejak & Badzińska, 2015;Lupo, 2015;Mbise & Tuninga, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A thorough review of the relevant academic literature revealed that HEIs acknowledge that for the sake of competitive advantage, their long-term success depends on the quality of services they render to their external stakeholders (Mbise & Tuninga, 2016;Surman et al, 2019). Thus, the quality of the educational services offered by public or PHEIs might be their strong strategy over others to gain a competitive advantage.…”
Section: Competitiveness In Higher Educationmentioning
confidence: 99%